2021
DOI: 10.3390/ijms221910851
|View full text |Cite
|
Sign up to set email alerts
|

Host–Viral Interactions in the Pathogenesis of Ulcerative Colitis

Abstract: Ulcerative colitis is characterized by relapsing and remitting colonic mucosal inflammation. During the early stages of viral infection, innate immune defenses are activated, leading to the rapid release of cytokines and the subsequent initiation of downstream responses including inflammation. Previously, intestinal viruses were thought to be either detrimental or neutral to the host. However, persisting viruses may have a role as resident commensals and confer protective immunity during inflammation. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 160 publications
(201 reference statements)
0
1
0
1
Order By: Relevance
“…Sua etiologia envolve interações entre o ambiente, desregulação do sistema imunológico, microbioma intestinal e uma predisposição genética à doença (SEGAL JP, et al, 2021). Essa desregulação imunológica foi por muito tempoatribuídaa uma imunidade adaptativa aberrante, enquanto estudos mais recentes apontam para um papel essencial das respostas imunes inatas do epitélio intestinal no desenvolvimento e perpetuação da inflamação (BRULAND T, et al, 2021). Quanto aos fatores genéticos, até o momento, mais de 200 polimorfismos de nucleotídeo único (SNPs) foram associados ao risco de desenvolver RCU (POPOV J, et al, 2021).…”
Section: Retocolite Ulcerativaunclassified
“…Sua etiologia envolve interações entre o ambiente, desregulação do sistema imunológico, microbioma intestinal e uma predisposição genética à doença (SEGAL JP, et al, 2021). Essa desregulação imunológica foi por muito tempoatribuídaa uma imunidade adaptativa aberrante, enquanto estudos mais recentes apontam para um papel essencial das respostas imunes inatas do epitélio intestinal no desenvolvimento e perpetuação da inflamação (BRULAND T, et al, 2021). Quanto aos fatores genéticos, até o momento, mais de 200 polimorfismos de nucleotídeo único (SNPs) foram associados ao risco de desenvolver RCU (POPOV J, et al, 2021).…”
Section: Retocolite Ulcerativaunclassified
“…It is unknown whether RNA signals derived from dead cells, such as damage-associated molecular patterns (DAMP), can impact antigen presentation in IECs. Additionally, whether viral infections in IBD can impact MHC-II expression is uninvestigated, particularly in the context of TNF ( 26 ). In a transcriptomic time-series screen using colonic HT-29 cells treated with TLR 1-9 ligands, NOD2 ligand, or cytokines (IL1β, IL10, TNFα), we found that TNF and TLR3 ligand Poly(I:C) that mimics viral and DAMP signals could upregulate MHC-I genes and MHC-II associated invariant chain CD74 ( 27 ).…”
Section: Introductionmentioning
confidence: 99%